2020 International Conference on Computational Science and Computational Intelligence (CSCI) 2020
DOI: 10.1109/csci51800.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

Toward Generating Synthetic CT Volumes using a 3D-Conditional Generative Adversarial Network

Abstract: We present a novel conditional Generative Adversarial Network (cGAN) architecture that is capable of generating 3D Computed Tomography scans in voxels from noisy and/or pixelated approximations and with the potential to generate full synthetic 3D scan volumes. We believe conditional cGAN to be a tractable approach to generate 3D CT volumes, even though the problem of generating full resolution deep fakes is presently impractical due to GPU memory limitations. We present results for autoencoder, denoising, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…As the diagnosis of COVID-19 using medical imaging has been a priority since the pandemic started, 39 (68%) of 57 studies reported the diagnosis of COVID-19 as the main focus of their work [ 19 - 21 , 23 - 33 , 35 - 37 , 39 , 41 , 42 , 44 , 46 , 50 , 52 , 53 , 55 , 56 , 58 - 60 , 63 - 69 , 71 , 72 ]. In addition, 9 (16%) studies reported data augmentation as the main task addressed in the work [ 18 , 43 , 45 , 49 , 54 , 61 , 62 ], 1 (2%) study reported prognosis of COVID-19 [ 22 ], 3 (5%) studies reported segmentation of lungs [ 34 , 51 , 57 ], and 1 (2%) study reported diagnosis of multiple lung diseases [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the diagnosis of COVID-19 using medical imaging has been a priority since the pandemic started, 39 (68%) of 57 studies reported the diagnosis of COVID-19 as the main focus of their work [ 19 - 21 , 23 - 33 , 35 - 37 , 39 , 41 , 42 , 44 , 46 , 50 , 52 , 53 , 55 , 56 , 58 - 60 , 63 - 69 , 71 , 72 ]. In addition, 9 (16%) studies reported data augmentation as the main task addressed in the work [ 18 , 43 , 45 , 49 , 54 , 61 , 62 ], 1 (2%) study reported prognosis of COVID-19 [ 22 ], 3 (5%) studies reported segmentation of lungs [ 34 , 51 , 57 ], and 1 (2%) study reported diagnosis of multiple lung diseases [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 3 (5%) studies used GANs for segmentation of the lung region within the chest radiology images [ 37 , 51 , 57 ], 3 (5%) studies used GANs for superresolution to improve the quality of the images before using them for diagnosis purposes [ 30 , 44 , 68 ], 5 (9%) studies used GANs for the diagnosis of COVID-19 [ 20 , 58 , 69 , 70 , 72 ], 2 (4%) studies used GANs for feature extraction from images [ 19 , 47 ], and 1 (2%) study used a GAN-based method for prognosis of COVID-19 [ 22 ]. The prevalent mode of imaging is the use of 2D imaging data, and 1 (2%) study reported a GAN-based method for synthesizing 3D data [ 49 ]. Figure 3 (see [ 18 - 74 ]) shows the mapping of the applications of GAN-based methods for all the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of related works that have investigated the use of GANs to improve the performance of COVID-19 screening from CT scans with reduced training volumes. However, to the best of our knowledge, all recent studies have made use of hundreds of positive cases for training [15], [16], [17], [19], [20]. Hundreds of cases, although small by deep learning standards, is still a substantial training volume to obtain during a pandemic, and the intent of CCS-GAN is to determine how advanced methods may be able to greatly reduce the number of positive images needed for potential future events.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [19] extended these approaches by combining GANs with ensemble learning and attention mechanisms. Mangalagiri et al also proposed an algorithm for generating 3D diagnostic quality COVID-19 CT scans with a conditional GAN architecture [20]. This method mainly focused on generating the entire CT volume through subdivision into blocks and focusing on blockwise synthesis rather than slice-wise synthesis.…”
Section: Related Workmentioning
confidence: 99%